Scalable photonic sources using two-dimensional lead halide perovskite superlattices - Jagielski, Jakub (Nat Commun, 2020)
Miniaturized photonic sources based on semiconducting two-dimensional (2D) materials offer new technological opportunities beyond the modern III-V platforms. For example, the quantum-confined 2D electronic structure aligns the exciton transition dipole moment parallel to the surface plane, thereby outcoupling more light to air which gives rise to high-efficiency quantum optics and electroluminescent devices. It requires scalable materials and processes to create the decoupled multi-quantum-well superlattices, in which individual 2D material layers are isolated by atomically thin quantum barriers. Here, we report decoupled multi-quantum-well superlattices comprised of the colloidal quantum wells of lead halide perovskites, with unprecedentedly ultrathin quantum barriers that screen interlayer interactions within the range of 6.5 Å. Crystallographic and 2D k-space spectroscopic analysis reveals that the transition dipole moment orientation of bright excitons in the superlattices is predominantly in-plane and independent of stacking layer and quantum barrier thickness, confirming interlayer decoupling.